The Solution:
Given:
We are required to solve for x and y by the Substitution Method.
Step 1:
Substitute the for y. This means we should equate both equations.
![3x+3=x-1](https://img.qammunity.org/2023/formulas/mathematics/college/bwwitvekabrhmrksgmcpxpu2tlodvv8lnp.png)
Solving for x in the above linear equation, we get:
![\begin{gathered} 3x-x=-1-3 \\ \\ 2x=-4 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/oh5uufxlbs0wwq8r96com1hn2sh701x17l.png)
Divide both sides by 2.
![\begin{gathered} (2x)/(2)=(-4)/(2) \\ \\ x=-2 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/hxckwjaxlqk81w5h8efj244rt45g6wdiwo.png)
Step 2:
Substitute -2 for x in any of the given equations.
![\begin{gathered} y=x-1 \\ y=-2-1 \\ y=-3 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/6031huqsoda4jcorz5ggyw1816ouu60r1r.png)
Thus, the correct answer is (-2, -3)